Resistência genética na cultivar Jalo Pintado 2 de feijão comum ao Colletotrichum lindemuthianum - Frias, Angélica Albuquerque Tomilhero (2014)
The anthracnose caused by fungus Colletotrichum lindemuthianum (Sacc. And Magnus) Briosi and Cavara is the most widespread disease and economically important fungal disease of common bean (Phaseolus vulgaris L.). The use of resistant cultivars is characterized as one of the most effective methods in controlling this disease. The present study had as objective to characterize the genetic resistance of the Andean common bean cultivar Jalo Pintado 2 to the C. lindemuthianum through inheritance and allelism tests. The experiment was conducted under greenhouse conditions at the Common Bean Breeding and Molecular Biology Laboratory of Núcleo de Pesquisa Aplicada à Agricultura (Nupagri). The results of segregation of the inheritance test of resistance in the F2 generation from the cross Jalo Pintado 2 (R) × Cornell 49-242 (S) inoculated with race 73 of C. lindemuthianum, adjusted the ratio of 3R: 1S. This ratio shows the action of a dominant gene in this cultivar Jalo Pintado 2. The allelism tests evidenced that the gene in of Jalo Pintado 2 is independent from the previously characterized: Co-1, Co-2, Co-3, Co-34, Co-4, Co-42, Co-43, Co-5, Co-6, Co-11, Co-12, Co-13, Co-14, Co-15 and Co-16. This gene is also independent those genes not yet named present in Paloma, Perla and Amendoim Cavalo cultivars. The authors propose the Co-18 symbol to designate the new gene for resistance to anthracnose.